THE DYNAMICS CONTROL OF THE RIGID WING UAV BY THE EXAMPLE OF USING LQR, LQG AND NONLINEAR CONTROL METHODS - A. A. Sclyarov; A. Ingabire (Современная наука и инновации)
Small - sized fixed-wing unmanned aerial vehicles (UAVs) have become a popular research topic in recent years.